Introduction: Urban friendship networks: Affective negotiations and potentialities of care. - Kathiravelu, Laavanya; Bunnell, Tim (Urban Studies (Sage Publications, Ltd.), 2018)
Issues of integration, assimilation and the place of ‘strangers’ within metropolitan contexts have been overwhelmingly conceptualised within the larger structural frames of ethnicity, nationality, immigration status and socio-economic class. This raises and reflects important issues around strategies of differentiation, urban exclusion and the hierarchies inherent in everyday life within contemporary cities. However, in privileging such modes of analysis, other more dynamic, elastic, latent and surreptitious forms of affinity, relatedness and connection within the urban environment are often left unexamined. Friendship is one of these. The articles in this special issue initiate a deeper and more sustained focus on friendship as a relational modality that characterises many urban interactions, and that also takes on particular forms within demographically diverse city spaces. The particular contribution of this special issue is in bringing together the literature from urban studies, research on diversity, understandings of social capital and networks and contemporary discussions of friendship. This introduction to the special issue argues that adopting alternative frameworks of enquiry such as friendship can serve to unsettle a priori assumptions about co-ethnic solidarity, and provide alternative epistemological starting points in understanding social networks. In doing so, this research not only contributes to contemporary readings of diverse cities but extends understandings of the routine affective and material labour that urban dwellers regularly undertake. Calling for a focus on informal bonds like friendship, this article suggests that it is within such unexplored spheres that possibilities of care and convivial city living exist.